Pengaruh Bimbingan Guru Pendidikan Agama Kristen Terhadap Moral Siswa Kelas X SMK Negeri 1 Palipi Tahun Pembelajaran 2022/2023 - Brigita Indah Sari; Wilson Simanjuntak; Nisma Simorangkir (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2023)
The aim of this research is to determine the positive and significant influence of Christian Religious Education teacher guidance on the morale of class X students at SMK Negeri 1 Palipi for the 2022/2023 academic year. The research method used is a quantitative research method. The population is all 122 class Data was collected using a positive closed questionnaire with 55 items, namely 22 items for variable /2023: 1) Test the analysis requirements: a) positive relationship test obtained rxy = 0.587 > rtable(=0.05,n=40) = 0.312. b) Testing a significant relationship obtained tcount= 4.474 > ttable(=0.05, dk=n-2=38)= 2.021. 2) Influence test: a) Regression equation test, obtained regression equation. b) Regression coefficient of determination test (r2) = 34.5%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable=(=0.05, dk numerator k=21, dk denominator=n-2=40-2=38) namely 19.98 > 1.51. Thus, Ha, namely that there is a positive and significant influence of Christian Religious Education teacher guidance on the morale of class